Hubungan Tingkat Pengetahuan dan Dukungan Keluarga Terhadap Kepatuhan Medikasi Diabetes Mellitus Tipe 2 di Puskesmas Kecamatan Limo Depok - Verawaty Melisa; Dayan Hasni; Toto Suharyanto (Malahayati Nursing Journal, 2023)
ABSTRACT Diabetes mellitus is a symptomatic metabolic disease characterized by elevated blood glucose levels due to impaired insulin release and decreased insulin performance. One of the successes of treatment in patients with Diabetes Mellitus (DM) was seen from controlled blood sugar levels. Controlled blood sugar levels are influenced by diet, physical activity, medication adherence and knowledge. This study aims to identify the characteristics of respondents related to age, gender, employment status, recent education, and length of suffering. As well as to understand the relationship between the level of knowledge and family support for medical compliance for people with Type 2 DM. Type of quantitative research, descriptive research design with a cross sectional approach. The sample of this study used Type 2 Diabetes Mellitus patients at the Puskesmas Limo Depok District and found a minimum sample number of 67 respondents. In this study, researchers used probability sampling. The characteristics of respondents were mostly female as many as 52 respondents (77.6%), ages 55-64 years 37 respondents (55.2%), employment as IRT 46 respondents (68.7%), primary education 32 respondents (47.8%). As well as the length of time patients suffered from Diabetes Mellitus for 1-4 years 58 respondents (86.6%). And most of the Type 2 Diabetes Mellitus patients had a high level of knowledge of 49 respondents (73.1%), had good family support of 45 respondents (67.2%), and compliance with 47 respondents (70.1%). There is a significant relationship between the level of knowledge on the adherence of type 2 diabetes mellitus medicine at the Limo Depok District Health Center with a p-value of 0.000. There is a significant relationship between family support and compliance with diabetes mellitus type 2 medicine at the Limo Depok District Health Center with a p-value of 0.000. It is hoped that the Puskesmas can provide education to families about the importance of family support for diabetes mellitus type 2 medical compliance so that informational support can be fulfilled. Keywords : Diabetes Mellitus Type 2, Family Support, Medication Compliance, Level of knowledge  ABSTRAK Diabetes mellitus ialah penyakit metabolik bergejala akan tertandai dengan meningginya tingkat glukosa di darah dikarenakan oleh gangguan pengeluaran insulin serta menurunnya kinerja insulin. Keberhasilan pengobatan pada pasien Diabetes Mellitus (DM) salah satunya dilihat dari terkendalinya kadar gula darah. Terkendalinya kadar gula darah ini dipengaruhi oleh faktor diet, aktivitas fisik, kepatuhan medikasi dan tingkat pengetahuan.: Penelitian ini bertujuan untuk mengidentifikasi karakteristik responden terkait umur, jenis kelamin, status pekerjaan, pendidikan terakhir, serta lama menderita. Serta untuk memahami hubungan tingkat pengetahuan dan dukungan keluarga terhadap kepatuhan medikasi bagi penderita DM Tipe 2. Jenis penelitian kuantitatif, desain penelitian deskriptif dengan pendekatan cross sectional. Sampel penelitian ini menggunakan pasien Diabetes Mellitus Tipe 2 di Puskesmas Kecamatan Limo Depok dan didapati jumlah sampel minimal sebanyak 67 responden. Pada penelitian ini, peneliti menggunakan probability sampling. Karakteristik responden sebagian besar berjenis kelamin perempuan sebanyak 52 responden (77,6%), usia 55-64 tahun 37 responden (55,2%), pekerjaan sebagai IRT 46 responden (68,7%), pendidikan terakhir SD 32 responden (47,8%). Serta lama pasien menderita Diabetes Mellitus selama 1-4 tahun 58 responden (86,6%). Dan sebagian besar pasien Diabetes Mellitus Tipe 2 memiliki tingkat pengetahuan tinggi 49 responden (73,1%), memiliki dukungan keluarga baik yaitu sebanyak 45 responden (67,2%), serta kepatuhan medikasi patuh 47 responden (70,1%). Ada hubungan signifikan anatar tingkat pengetahuan terhadap kepatuhan medikasi diabetes mellitus tipe 2 di Puskesmas Kecamatan Limo Depok dengan p-value 0,000. Ada hubungan signifikan hubungan dukungan keluarga terhadap kepatuhan medikasi diabetes mellitus tipe 2 di Puskesmas Kecamatan Limo Depok dengan p-value 0,000. Diharapkan untuk pihak Puskesmas dapat memberikan edukasi terhadap keluarga mengenai pentingnya dukungan keluarga terhadap kepatuhan medikasi diabetes mellitus tipe 2 sehingga dukungan informasional dapat terpenuhi. Kata Kunci: Diabetes Mellitus Tipe 2, Dukungan Keluarga, Kepatuhan Medikasi, Tingkat Pengetahuan